Pengaruh Kualitas Jasa dan Keputusan Konsumen Terhadap Loyalitas Konsumen Pada PT Sekawan Jaya Lestari - Muhamad Affan; Muhajirin Muhajirin (Journal of Business and Economics Research (JBE), 2020)
Services are a part of human needs that are very much needed by humans, for now the service sector provides a good contribution to economic growth both nationally and internationally. This study aims to determine the effect of service and consumer decisions on consumer loyalty at PT Sekawan Jaya Lestari Kota Bima. The sample used was 96 respondents. This type of research is associative with a quantitative approach. The technique of using data uses a questionnaire. Methods of data using simple random sampling method. The data analysis technique used validity test, reliability test, multiple regression analysis, and significant test. The results of this research indicate that: 1. There is an effect of service quality on consumer loyalty at PT Sekawan Jaya Lestari. 2. the influence of consumer decisions on consumer loyalty at PT Sekawan Jaya Lestari. 3. The influence of service quality and consumer decisions on consumer loyalty at PT Sekawan Jaya Lestari.